Biomarkers of traumatic brain injury. Literature review - Šmigelskytė , A.; Remenčiūtė , M.; Ragaišis , V. (Neurologijos seminarai, 2019)
Traumatic brain injury (TBI) is a structural injury of brain tissue or disruption of brain function due to an external force, which causes a decreased level of consciousness, loss of memory, alterations of mental state, and neurological deficits. Head computed tomography (CT) scan is a diagnostic modality of choice to evaluate patients for traumatic intracranial injuries. However, head CT scans are being overused in TBI patients. New biomarkers of TBI are being tested to avoid unnecessary head CT scans, diagnose TBI in a fast and efficient way, and determine its severity and prognosis. In the year of 2013, Scandinavian Neurotrauma Committee recommended S-100β for clinical use to predict intracranial injury on CT scans for suspected mild TBI. In the year of 2018, the US Food and Drug Administration approved a combination of GFAP and UCH-L1. Other biomarkers are also being tested for detecting TBI but they are not being used in medical practice yet.
Keywords: traumatic brain injury; computed tomography; biomarkers; ubiquitin C-terminal hydrolase-L1; glial fibrillary acidic protein; S-100 calcium-binding protein β; neuron specific enolase; myelin basic protein; Tau protein